The The Impact of Progressive Muscle Therapy on Anxiety Levels Among Pre-Anaesthesia Patients at RSI Banjarnegara: English - Lolandia Septin, Cita; Lintang Suryani, Roro; Utami, Tin; Suandika, Made (Global Indonesia Health Care (GOICARE), 2023)
Purpose: Determine the effect of progressive muscle therapy on the anxiety level of pre-anesthesia patients at RSI Banjarnegara. Methods: This type of research is pre experiment pre test and post test with one group design. The sample technique in this study used purposive sampling of 37 pre-anesthesia patients. Data were taken using measurements of anxiety before and after progressive muscle therapy. This research instrument used questionnaires and SOP for progressive muscle therapy. Result: The anxiety level of respondents before being given progressive muscle therapy was the majority of 26 respondents (70.3%) experienced moderate anxiety. The anxiety level of respondents after being given progressive muscle therapy was the majority of 20 respondents (54.1%) experienced mild anxiety. The results of data analysis in this study with paired t test showed a value of (p) 0.000 ˂ 0.05. Conclusion: This shows that there is a significant influence on the provision of progressive muscle therapy at RSI Banjarnegara. Based on the results of the study, it is expected that the Banjarnegara RSI service will use progressive muscle therapy to reduce pre-anesthesia anxiety levels